Analysis of the Average Difference Test of Production and Income of Several Sweet Potato Varieties Farming in Merauke - Ginting, Nina Maksimiliana; Fachrizal, Riza; Panga, Nurhaya; Redu, Silas Tanggu (International Journal of Agriculture System, 2023)
This study aims to calculate the production and income derived from farming several sweet potato varieties. The research was conducted in Bersehati Village, Tanah Miring District, Merauke Regency. The Research location was chosen purposively with the consideration that Kampung Bersehati is the largest sweet potato producing area in Merauke Regency. In total there are 157 sweet potato farmer populations, the number of samples taken was 20% of the population or 31 farmers. Data analysis was conducted using the concept of cost, revenue, farm income, feasibility and analysis of the average difference test. The results showed that the yield per growing season of the Cakar variety (1,603 kg) was higher than the Local variety (1,599 kg). However, farming the Local variety yielded a higher income (IDR 4,672,140.96) than the Cakar variety (IDR 4,475,777.98) at a selling price of IDR 6,000 per kg. The feasibility analysis showed that both the Local variety (R/C Ratio 1.95) and the Cakar variety (1.87) are worth trying. The difference test analysis revealed significant differences in production and income between the two varieties.